Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population. - Bevilacqua, Lorenzo; Navarra, Chiara O; Pirastu, Nicola; Lenarda, Roberto Di; Gasparini, Paolo; Robino, Antonietta (J Periodontal Res, 2018)
BACKGROUND AND OBJECTIVE: Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. METHODS: Diagnosis of chronic periodontitis was made following the criteria of the American Academy of Periodontology. Patients with chronic periodontitis were grouped into different categories: slight, severe, localized and generalized. A control group composed by people without signs of periodontitis or gingivitis was defined. DNA was genotyped using 370k Illumina chips. Linear mixed model regression was used to test the association between each single nucleotide polymorphism (SNP) (independent variable) and the periodontitis status (dependent variable), controlling for confounders sex, age and smoking. The genomic kinship matrix was also used as random effect. RESULTS: Four SNPs on the gene EFCAB4B resulted significantly associated to localized periodontitis (P < 5 × 10 ), with the best hit on the rs242016 SNP (P = 1.5 × 10 ). CONCLUSION: We have identified a novel significant association between the EFCAB4B gene and localized periodontitis. These results open a new perspective in the understanding of genetic factors contributing to this common disorder.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium-Binding Proteins; Chronic Periodontitis; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Young Adult

Investigation of the link between PROP taste perception and vegetables consumption using FAOSTAT data. - Mezzavilla, Massimo; Notarangelo, Michela; Concas, Maria Pina; Catamo, Eulalia; Gasparini, Paolo; Grillotti, Maria Gemma; Robino, Antonietta (Int J Food Sci Nutr, 2018)
In this work we investigated, in populations located in Central Asia, the relationship between PROP taste perception and vegetables liking and consumption using FAOSTAT dataset. Collected data were analysed using distance matrices, Mantel test and Pearson correlation. Populations showing similar ability in tasting PROP bitterness are more similar as respect to vegetable consumption (r = 0.63, p-value = .05). Moreover, a significant negative correlation was found between the percentage of Non Taster (NT) in different countries and the percentage of vegetable consumption (r = -0.87, p-value = .02), while a significant positive correlation emerged between the percentage of Super Taster (ST) and the percentage of vegetable liking (r = 0.87, p-value = .02). In our work we showed that differences in bitter perception among populations contributes to differences in vegetable liking and vegetable consumption. More in detail, populations with higher percentage of ST consume more vegetables than population where the majority of individuals are NT.

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

A Genome-Wide Association Study in isolated populations reveals new genes associated to common food likings. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia; Toniolo, Daniela; Gasparini, Paolo (Rev Endocr Metab Disord, 2016)
Food preferences are the first factor driving food choice and thus nutrition. They involve numerous different senses such as taste and olfaction as well as various other factors such as personal experiences and hedonistic aspects. Although it is clear that several of these have a genetic basis, up to now studies have focused mostly on the effects of polymorphisms of taste receptor genes. Therefore, we have carried out one of the first large scale (4611 individuals) GWAS on food likings assessed for 20 specific food likings belonging to 4 different categories (vegetables, fatty, dairy and bitter). A two-step meta-analysis using three different isolated populations from Italy for the discovery step and two populations from The Netherlands and Central Asia for replication, revealed 15 independent genome-wide significant loci (p < 5 × 10(-8)) for 12 different foods. None of the identified genes coded for either taste or olfactory receptors suggesting that genetics impacts in determining food likings in a much broader way than simple differences in taste perception. These results represent a further step in uncovering the genes that underlie liking of common foods that in the end will greatly help understanding the genetics of human nutrition in general.

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

Non-additive genome-wide association scan reveals a new gene associated with habitual coffee consumption. - Pirastu, Nicola; Kooyman, Maarten; Robino, Antonietta; van der Spek, Ashley; Navarini, Luciano; Amin, Najaf; Karssen, Lennart C; van Duijn, Cornelia M; Gasparini, Paolo (Sci Rep, 2016)
Coffee is one of the most consumed beverages world-wide and one of the primary sources of caffeine intake. Given its important health and economic impact, the underlying genetics of its consumption has been widely studied. Despite these efforts, much has still to be uncovered. In particular, the use of non-additive genetic models may uncover new information about the genetic variants driving coffee consumption. We have conducted a genome-wide association study in two Italian populations using additive, recessive and dominant models for analysis. This has uncovered a significant association in the PDSS2 gene under the recessive model that has been replicated in an independent cohort from the Netherlands (ERF). The identified gene has been shown to negatively regulate the expression of the caffeine metabolism genes and can thus be linked to coffee consumption. Further bioinformatics analysis of eQTL and histone marks from Roadmap data has evidenced a possible role of the identified SNPs in regulating PDSS2 gene expression through enhancers present in its intron. Our results highlight a novel gene which regulates coffee consumption by regulating the expression of the genes linked to caffeine metabolism. Further studies will be needed to clarify the biological mechanism which links PDSS2 and coffee consumption.

Understanding the role of personality and alexithymia in food preferences and PROP taste perception. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; La Bianca, Martina; Gasparini, Paolo; Carlino, Davide; Tepper, Beverly J (Physiol Behav, 2016)
Taste perception and food preferences are influenced by a variety of factors, including personality characteristics. The aims of this study were to examine the role of personality characteristics, such as alexithymia (a personality construct characterized by inability to identify, describe, and work with one's own feelings), in: 1) taste responses to the bitter genetic taste-marker PROP and 2) food liking. We studied 649 healthy subjects residing in six genetically-isolated villages of Northeast Italy. Data on PROP taste responsiveness, food liking, personality characteristics and TAS2R28 genotypes were collected. Results showed that PROP non-tasters had higher alexithymia scores than PROP tasters. Moreover, the presence of alexithymia in heterozygous individuals for the rs1726886 polymorphism of the TAS2R38 gene was associated with a reduction in the perceived intensity of PROP. Finally, higher alexithymia scores were associated with liking of alcohol, sweets and fats/meats whereas lower alexithymia scores were related to liking of vegetables, condiments and strong cheeses, Measures of temperament, character, anxiety and depression were also related to food liking. Our findings suggest that: 1) alexithymia, in addition to the TAS2R38 polymorphism, may play a role in responsiveness to the aversive and bitter taste of PROP; and 2) alexithymia, in combination with other personality traits, may provide important insights for better understanding food liking.

Analysis of functional variants reveals new candidate genes associated with alexithymia. - Mezzavilla, Massimo; Ulivi, Sheila; Bianca, Martina La; Carlino, Davide; Gasparini, Paolo; Robino, Antonietta (Psychiatry Res, 2015)
In this study we explored the possible association between 36,915 functional variants and alexithymia, a personality trait characterized by the inability to identify and describe emotions and feelings. From our analysis, variants in the genes ABCB4, TP53AIP1, ARHGAP32 and TMEM88B were identified linked to the alexithymia phenotype.
Keywords: Adolescent; Adult; Affective Symptoms; Aged; Case-Control Studies; DNA-Binding Proteins; Emotions; Female; Humans; Male; Membrane Proteins; Middle Aged; P-Glycoproteins; Personality Inventory; Phenotype; Tumor Suppressor Proteins; Young Adult

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Genome-wide association analysis on five isolated populations identifies variants of the HLA-DOA gene associated with white wine liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia M; Toniolo, Daniela; Gasparini, Paolo (Eur J Hum Genet, 2015)
Wine is the most popular alcoholic beverage around the world and because of its importance in society has been widely studied. Understanding what drives its flavor has been a quest for decades but much is still unknown and will be determined at least in part by individual taste preferences. Recently studies in the genetics of taste have uncovered the role of different genes in the determination of food preferences giving new insight on its physiology. In this context we have performed a genome-wide association study on red and white wine liking using three isolated populations collected in Italy, and replicated our results on two additional populations coming from the Netherland and Central Asia for a total of 3885 samples. We have found a significant association (P=2.1 × 10(-8)) between white wine liking and rs9276975:C>T a polymorphism in the HLA-DOA gene encoding a non-canonical MHC II molecule, which regulates other MHC II molecules. The same association was also found with red wine liking (P=8.3 × 10(-6)). Sex-separated analysis have also revealed that the effect of HLA-DOA is twice as large in women as compared to men suggesting an interaction between this polymorphism and gender. Our results are one of the first examples of genome-wide association between liking of a commonly consumed food and gene variants. Moreover, our results suggest a role of the MHC system in the determination of food preferences opening new insight in this field in general.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Polymorphisms in sweet taste genes (TAS1R2 and GLUT2), sweet liking, and dental caries prevalence in an adult Italian population. - Robino, Antonietta; Bevilacqua, Lorenzo; Pirastu, Nicola; Situlin, Roberta; Di Lenarda, Roberto; Gasparini, Paolo; Navarra, Chiara Ottavia (Genes Nutr, 2015)
The aim of the study was to assess the relationship between sweet taste genes and dental caries prevalence in a large sample of adults. In addition, the association between sweet liking and sugar intake with dental caries was investigated. Caries was measured by the decayed, missing, filled teeth (DMFT) index in 647 Caucasian subjects (285 males and 362 females, aged 18-65 years), coming from six villages in northeastern Italy. Sweet liking was assessed using a 9-point scale, and the mean of the liking given by each individual to specific sweet food and beverages was used to create a sweet liking score. Simple sugar consumption was estimated by a dietary history interview, considering both added sugars and sugar present naturally in foods. Our study confirmed that polymorphisms in TAS1R2 and GLUT2 genes are related to DMFT index. In particular, GG homozygous individuals for rs3935570 in TAS1R2 gene (p value = 0.0117) and GG homozygous individuals for rs1499821 in GLUT2 gene (p value = 0.0273) showed higher DMFT levels compared to both heterozygous and homozygous for the alternative allele. Furthermore, while the relationship sugar intake-DMFT did not achieve statistical significance (p value = 0.075), a significant association was identified between sweet liking and DMFT (p value = 0.004), independent of other variables. Our study showed that sweet taste genetic factors contribute to caries prevalence and highlighted the role of sweet liking as a predictor of caries risk. Therefore, these results may open new perspectives for individual risk identification and implementation of target preventive strategies, such as identifying high-risk patients before caries development.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

A population-based approach to study the impact of PROP perception on food liking in populations along the Silk Road. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; Dognini, Maddalena; Tepper, Beverly J; Gasparini, Paolo (PLoS One, 2014)
Taste is one of the main factors determining food choices. Differences in PROP bitter taste perception have been implicated in individual differences in food preferences and selection. The present study examined associations between, PROP phenotypes, self-reported food liking and TAS2R38 polymorphisms, the major gene implicated in PROP bitterness, in six different populations of the Caucasus and Central Asia, located along the ancient Silk Road. Differences in the distribution of PROP phenotypes across populations were detected, with a higher frequency of super tasters in Tajikistan (31.3%) and Armenia (39.0%) and a higher frequency of non tasters in Georgia (50.9%). While no relationships were observed between PROP phenotypes and food liking using standard statistical tests, we used an approach based on comparison of distance matrices derived from these data. The first matrix compared the food liking ratings of each population to all others pairwise using the Kruskal-Wallis test (at p<0.00063), and the second one compared the distribution of PROP phenotypes across all populations in a similar manner calculating the chi-square statistic as a distance measure. A strong correlation between the two matrices was found (Mantel test: r = 0.67, p-value = 0.03), suggesting that the pattern of food liking across populations was closely related to the distribution of PROP phenotypes. This same relationship was not observed when TAS2R38 genotypes were substituted for PROP phenotypes in this analysis. Our data suggest that a population-based approach utilizing distance matrices is a useful technique for detecting PROP-related differences in food liking and can be applied to other taste phenotypes.
Keywords: Armenia; Azerbaijan; Food; Genetic Association Studies; Genotype; Haplotypes; Humans; Polymorphism, Single Nucleotide; Propylthiouracil; Receptors, G-Protein-Coupled; Tajikistan; Taste; Taste Perception; Uzbekistan

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Genetics of food preferences: a first view from silk road populations. - Pirastu, Nicola; Robino, Antonietta; Lanzara, Carmela; Athanasakis, Emmanouil; Esposito, Laura; Tepper, Beverly J; Gasparini, Paolo (J Food Sci, 2012)
Food preferences are the main factor driving food intake and choice. There are good reasons to suspect some genetic influence on food acceptance, not least because genetic factors are implicated in a number of factors that are likely to be related to food choice. In addition, some food dislikes show themselves early in life, before there is any evidence for aversive experiences. Although taste has been widely studied in regards of pure tastes such as bitter or sweet perception, the relationship between taste-related genes and food preferences has seldom been explored. In this work we investigated relationship of 37 taste-related genes with food preferences. The study was carried out during a scientific expedition through Caucasus and Central Asia (Silk Road) analyzing more than 400 samples from 5 different countries. A food preference questionnaire was administered to each participant and a DNA sample was obtained. Other information, such as age, sex, life style and anthropometrical measures, were also collected. We found significant associations with variants of: (1) TAS1R2 [Correction added after initial online publication on 27 Aug 2012. TAS1R3 was changed to TAS1R2.] gene and liking of Vodka (P= 1.6 × 10(-3)), white wine (P= 4.0 × 10(-4)) and lamb meat (P= 1.6 × 10(-3)); (2) PCLB2 gene and preference for Hot Tea (P= 8.0 × 10(-4)); (3) TPRV1 gene and beet liking (P= 3.8 × 10(-5)); and (4) ITPR3 gene and liking of both lamb meat (5.8 × 10(-4)) and sheep cheese (8.9×10(-4)). These findings give a new insight on a better understanding, of genetic factors influencing food preferences which is critical to the development of effective dietary interventions, especially for people that may be genetically not predisposed for liking specific nutrients.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Azerbaijan; Child; Choice Behavior; Cohort Studies; Female; Food Habits; Food Preferences; Gene Frequency; Genotype; Georgia; Humans; Kazakhstan; Linear Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Questionnaires; Tajikistan; Taste; Uzbekistan; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide